2001
DOI: 10.1203/00006450-200105000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Leptin Influences Birth Weight in Twins with Discordant Growth

Abstract: The objective of this study was to determine the plasma leptin concentrations in twin pregnancies in relation to chorionicity and discordant fetal growth. We studied 53 twin pregnancies of which 26 had growth discordance of Ն20% and 27 were concordant for growth (discordance of Յ10%). Paired maternal and fetal blood samples were obtained at birth. Plasma leptin concentrations were measured by RIA. In discordant monochorionic pregnancies, fetal plasma leptin concentrations in the intrauterine growth-restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…We found that in uncomplicated concordant-weight multifetal pregnancies, as in singleton pregnancies, the umbilical cord leptin levels correlated well only with the birth weight. Recent data collected from a population of discordant sets of twin pregnancies [34] support the theory of the placental factors, rather than maternal, influencing the leptin secretion. Uniquely, we found by studying the umbilical vein leptin levels in triplets this correlation to be unaffected by chorionicity or by the number of fetuses in the set.…”
Section: Discussionmentioning
confidence: 82%
“…We found that in uncomplicated concordant-weight multifetal pregnancies, as in singleton pregnancies, the umbilical cord leptin levels correlated well only with the birth weight. Recent data collected from a population of discordant sets of twin pregnancies [34] support the theory of the placental factors, rather than maternal, influencing the leptin secretion. Uniquely, we found by studying the umbilical vein leptin levels in triplets this correlation to be unaffected by chorionicity or by the number of fetuses in the set.…”
Section: Discussionmentioning
confidence: 82%
“…The presence of a placenta-specific upstream enhancer on the gene suggests that it is regulated differently from that of adipose origin [52,53]. Studies in humans have shown a correlation between cord blood and placental leptin, but not between maternal leptin and birth weight [30,54] (reviewed in [32]). This suggests that placental leptin may promote fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, insulin is an inducer of leptin production in human placenta as shown in vivo [84], enhancing the activity of leptin promoter region [85]. This may be relevant in gestational diabetes [6,86,112,127], a state of greater insulin resistance and hyperinsulinemia than normal pregnancies. In this line, numerous studies have reported that circulating leptin levels, as well as placental leptin and LEPR expression are significantly higher in pregnant women with GDM compared to healthy control women with uncomplicated pregnancy [128,129], providing, at least, a molecular mechanism for the placenta overgrowth previously observed in GDM [99,100].…”
Section: Role Of Leptin In Pregnancymentioning
confidence: 99%